2002
DOI: 10.1124/jpet.301.1.315
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Interactions of Dopamine and Dobutamine with Human Catechol-O-methyltransferase and Monoamine Oxidase in Vitro

Abstract: Dopamine and dobutamine are often infused together into acutely ill patients requiring temporary support of cardiac and renal function, but whether these catecholamines affect the metabolic clearance of each other is not established. We determined the kinetics of dopamine and dobutamine as substrates and inhibitors of each other, i.e., apparent V max , K m , and K i , with crude preparations of human blood mononuclear cell catechol-O-methyltransferase (COMT) and platelet monoamine oxidase (MAO) at pH 7.4 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…There are significant differences in β‐adrenergic receptor density in different parts of the heart,23,28,29 distribution of degrading enzymes, and local metabolism. Catechol‐O‐methyltransferase (COMT), the primary enzyme responsible for dobutamine degradation,30,31 is 10‐fold less active in the right atrium than in the left ventricle 32. Other studies have shown a regional variation in COMT activity in different chambers of the heart 33.…”
Section: Discussionmentioning
confidence: 99%
“…There are significant differences in β‐adrenergic receptor density in different parts of the heart,23,28,29 distribution of degrading enzymes, and local metabolism. Catechol‐O‐methyltransferase (COMT), the primary enzyme responsible for dobutamine degradation,30,31 is 10‐fold less active in the right atrium than in the left ventricle 32. Other studies have shown a regional variation in COMT activity in different chambers of the heart 33.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies also provided evidence that COMT activity in human blood mononuclear cell preparations reflects that found in human red blood cells, which in turn have been used extensively to characterize the genetics of human COMT (Weinshilboum et al, 1999). Recent kinetic studies with the human mononuclear cell preparation reveal that dobutamine and dopamine act as competitive inhibitors of each other for COMT activity and that dobutamine serves as the better substrate, largely due to its lower apparent K m (0.05 versus 0.44 mM) (Yan et al, 2002). These observations are in accord with a recent structure-activity kinetic study that showed that both catecholamines serve as substrates for a human recombinant COMT enzyme (Lautala et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine is inactivated by oxidative deamination by mitochondrial monoamine oxidase and by O-methylation by catechol-O-methyltransferase. This rapid enzymatic degradation accounts for a half-life of a few minutes when dopamine is circulating in the blood (32,33). Dopamine's ability to protect against cold preservation injury depends on its diffusion into cells (34).…”
Section: Clinical Outcomesmentioning
confidence: 99%